2017
DOI: 10.1097/mat.0000000000000476
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Recombinant Antithrombin III in Pediatric and Neonatal ECMO Patients

Abstract: A retrospective review of 77 pediatric and neonatal extracorporeal membranous oxygenation (ECMO) patients who received recombinant antithrombin III (ATIII) for ATIII activity greater than 80% was conducted. Anticoagulation management was per institutional protocol. An ATIII activity greater than 80% was targeted. Diagnosis, reason for ECMO cannulation, blood product usage, heparin dosing, ATIII activity and doses, thrombotic and bleeding complications, hours on ECMO, and mortality were recorded. We calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 19 publications
0
41
0
Order By: Relevance
“…When evaluating the administration of one vial of AT (1,000 U; averaging 241 U/kg) Ryerson et al also reported no adverse events, though it is important to note that heparin dose was decreased by 50% at the time of administration (18). Other studies have confirmed lack of bleeding complications associated with AT treatment (20). Tighter control of anticoagulation with AT replacement is also reported; however, this did not affect the longevity of the ECMO circuit (17).…”
Section: Coagulation Evaluation and Managementmentioning
confidence: 76%
“…When evaluating the administration of one vial of AT (1,000 U; averaging 241 U/kg) Ryerson et al also reported no adverse events, though it is important to note that heparin dose was decreased by 50% at the time of administration (18). Other studies have confirmed lack of bleeding complications associated with AT treatment (20). Tighter control of anticoagulation with AT replacement is also reported; however, this did not affect the longevity of the ECMO circuit (17).…”
Section: Coagulation Evaluation and Managementmentioning
confidence: 76%
“…Another problem is heparin resistance related to reliance on ATIII levels which are lower in critically ill children and neonates and UFH's inability to inhibit factor Xa bound to platelets (56). Evidence suggests that ATIII activity often decreases over time in children on ECMO (5760). Many centers routinely replace ATIII in an attempt to maximize heparin effect.…”
Section: Anticoagulation Strategiesmentioning
confidence: 99%
“…ATIII can be supplemented by transfusion of fresh frozen plasma or by infusing ATIII concentrates. But, ATIII concentrates are expensive and studies in the neonatal and pediatric population have found mixed results when ATIII supplementation is utilized (5760). A recent large observational report (including 5,360 neonates) found that ECMO patients supplemented with ATIII had an increased number of thrombotic and hemorrhagic events and longer hospital length of stay with no difference in mortality (61).…”
Section: Anticoagulation Strategiesmentioning
confidence: 99%
“…Heparin requires endogenous antithrombin III (AT3) to be effective; however, serum AT3 levels have been noted to be naturally low in neonatal populations and may also be low in those undergoing ECMO. 4,5 AT3 may be supplemented with either fresh frozen plasma or recombinant antithrombin products. 6,7 This practice is not standardized, may provide inconsistent anticoagulation results, and significantly increases the cost of heparin therapy.…”
Section: Introductionmentioning
confidence: 99%